Indonesia’s Sovereignty Discourse in the Flight Information Region (FIR) Agreement with Singapore over the Kepulauan Riau: A Literature Review - Iggel Alghufron D. Sumardi (Journal of Maritime Policy Science, 2026)
This article reassesses the discourse on Indonesian sovereignty in Indonesia-Singapore Flight Information Region (FIR) governance after the 2022 realignment and its entry into force on 21 March 2024. The study addresses a persistent analytical problem: public and academic debate often conflates territorial sovereignty, FIR responsibility, and delegated air navigation services (ANS). Using a structured integrative literature review with a qualitative approach, the study synthesizes 40 references, prioritizing peer-reviewed publications from 2016 to August 2026 and retaining indispensable primary legal and official documents. Evidence was examined through qualitative content analysis, reflexive thematic coding, cross-source comparison, and verification of legal claims against the Chicago Convention, ICAO materials, Presidential Regulation No. 109 of 2022, and bilateral implementation statements. The synthesis is organized around five domains: juridical sovereignty and technical delegation, state capacity, legal-operational consequences of the 2022 agreement, security and civil-military coordination, and public discourse. Findings show that the realignment did not transfer or restore territorial sovereignty in a legal sense; rather, it reconfigured FIR responsibility while preserving specified ANS delegation to Singapore. Recent research also indicates that effective sovereignty depends on regulatory coherence, technological readiness, inter-agency communication, stakeholder collaboration, civil-military interoperability, and diplomatic capacity. The article therefore proposes a distinction between formal sovereignty and effective sovereignty and develops a post-2024 evaluation agenda centered on oversight, data sharing, coordination, safety performance, and accountability. This framework offers a more precise basis for assessing Indonesia's airspace governance beyond symbolic claims of control.